Bridging Farmer and Researcher: Extension through the Eyes of Agents in Rural PakistanBridging Farmer and Researcher: Extension through the Eyes of Agents in Rural Pakistan - Sandra Heaney-Mustafa; Francesco Sofo; Mukaddas Afzal; Zubair Anwar; Bareerah Fatima; Faizan ul Hasan (Journal of International Agricultural and Extension Education, 2018)
Irrigation and efficient water usage by farmers remain keyagricultural problems in Pakistan. Technological approaches to water management specifically irrigation management using cloud technology is a recent innovation currently being trialed in Pakistan through a project conducted by the authors and funded by the Australian Centre for International Research. The paper reports on the perceptions of rural agents in Pakistan involved in the scaling out of new technologies to improve irrigation practices of a large number of farmers. The methodology adopted the use of focus groups with water professionals and extension agents as this approach has been proven to be a keyeffective method to assist rural agents to gather current information on irrigation problems and the scaling out process. Eight focus groups were assembled with an average of ten participants in each group. The findings revealed the current practices, positive outcomes and challenges to conducting farmer education in Pakistan. The importance of this research is its potential toimproving work practices of large numbers of farmers that continue to be highly challenging. The study gives fresh insights on how farmer education methods could be achieved in relation to improving water irrigation through new technological practices of a significantly increased number of farmers.
Keywords: Farmer Field Schools (FFS); adult education; extension; irrigation technology; scaling out